3(3-2)+8*2=27-4*2

Simple and best practice solution for 3(3-2)+8*2=27-4*2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3-2)+8*2=27-4*2 equation:


Simplifying
3(3 + -2) + 8 * 2 = 27 + -4 * 2

Combine like terms: 3 + -2 = 1
3(1) + 8 * 2 = 27 + -4 * 2

Multiply 3 * 1
3 + 8 * 2 = 27 + -4 * 2

Multiply 8 * 2
3 + 16 = 27 + -4 * 2

Combine like terms: 3 + 16 = 19
19 = 27 + -4 * 2

Multiply -4 * 2
19 = 27 + -8

Combine like terms: 27 + -8 = 19
19 = 19

Add '-19' to each side of the equation.
19 + -19 = 19 + -19

Combine like terms: 19 + -19 = 0
0 = 19 + -19

Combine like terms: 19 + -19 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -16x^2+32x+20=0 | | c-7=10 | | -16x^2+32x+20=o | | -2(t+4.33)=9 | | x^2-xy+2y^2=4 | | 7-9x=-6x-22 | | 9+8(x-3)=17 | | 3x+100+2x-20=180 | | n^2+2n-760=0 | | -2(4x+2)+2x=20 | | (2x-3)+(3x+1)+2x=40 | | 3y^3=375 | | 2t(t+1)=t^3-5t | | k=7k | | 3(3-2)+8c=27-4c | | 3+1(-18x+5)+-6=24 | | -32=-7-X | | 75+29x-2+36x+2=360 | | 4x+3y=180equation | | w^2-26w+120=0 | | 1+8x=5x+4 | | x^3+y^3=35 | | 6x-2(5+1x)=2(2x+1)-8 | | 1.7+7x=9.5-4x | | 7+2(m-5)= | | 8a+10=2(5-4a) | | Rw+8n=ar | | m(x)=8x | | -3(2x+5)+x=15 | | 6x-2(5x+1)=2(2x+1)-8 | | 4c-2c+15=25 | | d(5+3-2x)= |

Equations solver categories